2001
DOI: 10.1108/eum0000000007279
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of apparel quality: outlet stores versus department stores

Abstract: Past research has shown that consumers believe there is a strong relationship between price and quality; they also believe there is a strong relationship between brand and quality. Therefore, when comparing similar pieces of apparel, items with a designer brand or a higher price are perceived, by most customers, to be of higher quality. The purpose of this study was to compare the pricing and quality of identical designer merchandise sold in department stores and manufacturers’ outlet stores. The researchers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The quality level of an item of clothing is a difficult factor to isolate and define when this item of clothing has to be evaluated. (Fowler & Clodfelter, 2001).…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality level of an item of clothing is a difficult factor to isolate and define when this item of clothing has to be evaluated. (Fowler & Clodfelter, 2001).…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
“…In many cases, men and women are not informed on how they should evaluate the items that make up the garments. (DeKlerk & Lubbe, 2008;Fowler & Clodfelter, 2001;Goldsmith & Goldsmith, 2002;Hye & Stoel, 2002;Pentecost & Andrews, 2010).…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar in form and development to SERVQUAL (Parasuraman, Zeithaml, & Berry, 1988), the development of the ApparEx scale began with the determination of eight potentially overlapping dimensions. Drawn from studies of consumer satisfaction/dissatisfaction with apparel items (Fowler & Clodfelter, 2001), texts documenting apparel manufacturing standards (Solinger, 1988) ', 1972), the eight proposed dimensions of apparel quality included: 1) garment care, or the means of maintaining a garment's original appearance; 2) durability, or the ability of a garment to retain its original proportions and condition over time; 3) color, or the ability of a garment to retain its original hue after wear and laundering/dry cleaning; 4) fabric, or the raw material (piece goods) from which a garment is constructed; 5) notions/trims/closures, or the materials or stitching which provide support or decorative detail for the outer shell of a garment, as well as the means for keeping a garment in place on the body; 6) construction/workmanship, or the process by which the various components are assembled into a finished garment; 7) fit, or the degree to which a garment conforms to or differs from the body; and 8) style/fashion, or the aesthetic appeal of a garment. The definition of these dimensions of the domain of apparel quality was intended to establish a basis for content validity of the scale.…”
Section: Scale Developmentmentioning
confidence: 99%
“…In an investigation into consumer use of criteria for evaluating women's apparel, Abraham‐Murali and Littrell (1995b) found that less than 4% of female apparel consumers pay attention to accessories such as trims, zippers and buttons. According to Fowler and Clodfelter (2001), garment construction entails the methods used to assemble the garment. Construction methods include seams, hems, darts, collars, sleeves and cuffs.…”
Section: Literature Reviewmentioning
confidence: 99%